Comparison of Whole Body Reaction Time Between Singles and Doubles Badminton Players Aged 14–17 Years - Muhammad, Mar'ie; Bahri, Samsul; Hasyim, Rafif Rifqi Naufal; Lituhayu, Kamilia (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
Whole Body Reaction Time (WBRT) is an important biomotor component in the performance of badminton athletes, especially in responding to unexpected stimuli during matches. This study aims to compare the WBRT between male singles and doubles badminton athletes aged 14–17 years. The research used a quantitative comparative approach with purposive sampling technique. The population consisted of 60 athletes at PB Taqi Arena, West Bandung Regency. Based on the inclusion criteria, 37 athletes were selected as samples, consisting of 18 singles and 19 doubles athletes. Data collection was conducted on May 3–4, 2025. Measurements included anthropometry (Omron Karada Scan HBF-375), height (Stature Meter OneMed HT701), and WBRT (Whole Body Reaction Measuring Equipment Takei TKK-5408). Shapiro–Wilk normality test results indicated normal distribution in both groups (p > 0.05). The average WBRT for singles athletes was 0.286 ± 0.024 seconds, while for doubles athletes it was 0.260 ± 0.021 seconds. The independent samples t-test showed a significant difference between the two groups (p = 0.002). These findings indicate that doubles athletes have better whole body reaction speed compared to singles athletes. This difference is likely influenced by tactical demands and playing patterns in doubles, which require quick responses to stimuli from both opponents and partners. These results can serve as a basis for designing specific training programs based on match type to optimally improve athletes' reaction performance. Keywords: badminton, reaction time, whole body reaction, singles and doubles events.